Study on the Impacts of Emergency on Economic, Environmental and Social Areas Using Mixed Methods Research - Jan Fuka; Robert Baťa; Kateřina Josková; Jiří Křupka (Emerging Science Journal, 2022)
Mixed methods research methodology appears to be a suitable approach for researching complex phenomena such as emergencies. Researchers study the impacts on different areas such as economy, society, or environment, mostly in separate studies. To better understand the reality of emergencies, it is necessary to study the problem in the broadest possible context. So, examining those impacts in one single study is a challenge. The objective of this article is to process a comprehensive assessment of an emergency that has the potential to establish the basis of a robust tool for public managers to support their decision-making, using mixed methods research methodology. The crisis is an explosion of an ammunition storage site in the Czech Republic - the former satellite country of the Soviet Union. The sub-methods used in mixed methods research are analysis of data, interviews, questionnaire surveys, and field research. The main findings include that in the economic area, growth of public budget expenditures was found; in the environmental area, primary and inducted impacts have been proved. Survey also confirms that the emergency reduced the personal sense of security and trust in public institutions in the affected community. Doi: 10.28991/ESJ-2022-06-01-07 Full Text: PDF